2022
DOI: 10.1155/2022/2915644
|View full text |Cite
|
Sign up to set email alerts
|

Ananas comosus Peels Extract as a New Natural Cosmetic Ingredient: Oil-in-Water (O/W) Topical Nano Cream Stability and Safety Evaluation

Abstract: Ananas comosus peels (AcP) are among the agro-industrial biomasses contributing to a significant volume of waste in Malaysia. Thus, the AcP extract (AcPE) may prove useful for other applications, such as an ingredient in a nanocream for controlled delivery for dermal application. Therefore, this study aimed to develop an oil-in-water (O/W) nanocream using ingredients derived from the AcPE and test its stability alongside safety evaluation. The extract is a rich source of polyphenolic compounds viz., catechin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Cosurfactants are often required because their free energy is higher than that of separate oil and water phases ( Cimino et al, 2021 ). Many studies have reported the use of surfactants and cosurfactants as emulsifiers in nanoemulsions of EOs in water, including poloxamer 188, lecithin, PluronicF68, Tween60, Tween80, decanoyl/octanoyl-glycerides, glycerin monostearate, span 8, and polyethylene glycol 400 ( PEG400 ) ( Shi et al, 2016 ; Cimino et al, 2021 ; Doungnapa et al, 2021 ; Singh et al, 2021 ; Yahya et al, 2022 ). In this study, Tween60 and Tween80 were used as surfactants, and PEG400 was used as a cosurfactant in the nanoemulsion-based formulations of different oils and their ratios, following the recommendations of Doungnapa et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
“…Cosurfactants are often required because their free energy is higher than that of separate oil and water phases ( Cimino et al, 2021 ). Many studies have reported the use of surfactants and cosurfactants as emulsifiers in nanoemulsions of EOs in water, including poloxamer 188, lecithin, PluronicF68, Tween60, Tween80, decanoyl/octanoyl-glycerides, glycerin monostearate, span 8, and polyethylene glycol 400 ( PEG400 ) ( Shi et al, 2016 ; Cimino et al, 2021 ; Doungnapa et al, 2021 ; Singh et al, 2021 ; Yahya et al, 2022 ). In this study, Tween60 and Tween80 were used as surfactants, and PEG400 was used as a cosurfactant in the nanoemulsion-based formulations of different oils and their ratios, following the recommendations of Doungnapa et al (2021) .…”
Section: Discussionmentioning
confidence: 99%